2007
DOI: 10.1017/s0959259808002384
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in older people: an update

Abstract: In the past two decades, the rate of surgery in older people has increased more rapidly than the rate of aging of the population, so both a larger proportion and a greater number of older people are now undergoing surgery. This may partly reflect a cultural change in surgery and anaesthesia with respect to a greater willingness to undertake elective procedures in older people, although there remain areas where they have less access to surgery than do younger patients. For instance, older people are less likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…From other studies comparing older surgical patients to younger patients, we hypothesize that functional decline, increased care requirements, decreased QOL, risk to cognition, and poor symptom control are more important concerns than survival time for patients aged 80 and over. 5,62,63 Our definition of patient-centered outcomes is based on these findings. Our study found that studies in aortic aneurysm surgery, despite being focused on patients aged 80 and over, rarely or never measured patient-centered values in their outcome indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From other studies comparing older surgical patients to younger patients, we hypothesize that functional decline, increased care requirements, decreased QOL, risk to cognition, and poor symptom control are more important concerns than survival time for patients aged 80 and over. 5,62,63 Our definition of patient-centered outcomes is based on these findings. Our study found that studies in aortic aneurysm surgery, despite being focused on patients aged 80 and over, rarely or never measured patient-centered values in their outcome indicators.…”
Section: Discussionmentioning
confidence: 99%
“…When complications arise, the consequences are often worse for older patients. 5,6 Older patients also have greater risk of specific complications such as delirium, falls, pressure sores, pneumonia, and decreased mobility. 5…”
Section: Introductionmentioning
confidence: 99%
“…9 Since then there have been a number of important advances with the publication of several guidelines and a growing evidence base. 9 Since then there have been a number of important advances with the publication of several guidelines and a growing evidence base.…”
Section: Introductionmentioning
confidence: 99%